2019
DOI: 10.1016/j.abb.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

PRMT7 as a unique member of the protein arginine methyltransferase family: A review

Abstract: Protein arginine methyltransferases (PRMTs) are found in a wide variety of eukaryotic organisms and can regulate gene expression, DNA repair, RNA splicing, and stem cell biology. In mammalian cells, nine genes encode a family of sequence-related enzymes; six of these PRMTs catalyze the formation of ω-asymmetric dimethyl derivatives, two catalyze ω-symmetric dimethyl derivatives, and only one (PRMT7) solely catalyzes ω-monomethylarginine formation. Purified recombinant PRMT7 displays a number of unique enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 95 publications
4
64
0
Order By: Relevance
“…Protein arginine methyltransferases (PRMTs) catalyze mono-methylation and symmetric or asymmetric di-methylation of arginine residues on both histone and non-histone substrates to modulate diverse biological processes, including transcription, cell signalling, mRNA translation, DNA damage repair signalling, receptor trafficking, protein stability and pre-mRNA splicing ( Jelinic et al, 2006 ; Bedford and Clarke, 2009 ; Dhar et al, 2012 ; Jeong et al, 2016 ; Blanc and Richard, 2017 ; Jeong et al, 2020 ). Protein Arginine Methyltransferase 7 (PRMT7) was reported as a type III PRMT to catalyze mono-methylation of arginine residues on both histone and non-histone substrates ( Bedford and Clarke, 2009 ; Karkhanis et al, 2012 ; Blanc and Richard, 2017 ; Jain and Clarke, 2019 ; Haghandish et al, 2019 ). Recent studies also reported that PRMT7 can symmetrically di-methylate proteins such as p38 and GLI2 ( Jeong et al, 2020 ; Vuong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Protein arginine methyltransferases (PRMTs) catalyze mono-methylation and symmetric or asymmetric di-methylation of arginine residues on both histone and non-histone substrates to modulate diverse biological processes, including transcription, cell signalling, mRNA translation, DNA damage repair signalling, receptor trafficking, protein stability and pre-mRNA splicing ( Jelinic et al, 2006 ; Bedford and Clarke, 2009 ; Dhar et al, 2012 ; Jeong et al, 2016 ; Blanc and Richard, 2017 ; Jeong et al, 2020 ). Protein Arginine Methyltransferase 7 (PRMT7) was reported as a type III PRMT to catalyze mono-methylation of arginine residues on both histone and non-histone substrates ( Bedford and Clarke, 2009 ; Karkhanis et al, 2012 ; Blanc and Richard, 2017 ; Jain and Clarke, 2019 ; Haghandish et al, 2019 ). Recent studies also reported that PRMT7 can symmetrically di-methylate proteins such as p38 and GLI2 ( Jeong et al, 2020 ; Vuong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reason may be that the three motifs in the N terminal catalytic domain are very important for the enzymatic activity. Dot mutations in these motifs have been reported to change the enzyme activity (Cáceres et al, 2018; Debler et al, 2016; Feng, Hadjikyriacou, & Clarke, 2014; Hasegawa et al, 2014; Jain & Clarke, 2019). These results suggest that medaka Prmt7 may play similar roles with the PRMT7 in other species.…”
Section: Discussionmentioning
confidence: 99%
“…In human, it was also found that two male sibs with a homozygous PRMT7 mutation presented with an early intrauterine growth restriction. The patients with PRMT7 mutations showed sensorineural hearing loss, severe intellectual disability, genitourinary involvement, and global developmental delay after birth (Birnbaum et al, 2019;Jain & Clarke, 2019). In Xenopus, prmt7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The type III PRMT (PRMT7) catalyzes only the monomethyl arginine of specific arginine residues. Arginine methylation by PRMTs is involved in gene transcription, pre-mRNA splicing, signal transduction, DNA damage response, and cell fate decisions [33][34][35].…”
Section: Overview Of the Prmt Family Of Proteinsmentioning
confidence: 99%